Odpowiedzi

2010-03-14T16:40:35+01:00
A)-3x-2x=-10
-5x=-10
x=2
b)2x-2=7-x
3x=9
x=3
c)10=4-2x
6=-2x
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=3
x=-1.5
e)2(x+1)=x
2x+2=x
x=-2
Najlepsza Odpowiedź!
2010-03-14T16:41:37+01:00
A)
-3x = 2x - 10|-2x
-5x = -10|:5
-x = -2|* (-1)
x = 2
b)
2x - 2 = 7 - x|+ x
3x - 2 = 7|+2
3x = 9|:3
x = 3
c)
10 = 4 - 2x|+2x
2x + 10 = 4|-10
2x = -6|2
x = -3
d)
-(2x - 1) = 4
-2x + 1 = 4|-1
-2x = 3|:2
-x = 3/2|* (-1)
x = -3/2
x = -1(i) 1/2
e)
2(x + 1) = x
2*x + 2*1 = x
2x + 2 = x|- 2x
2 = -x|* (-1)
-2 = x